Containing Nationalism: Culture, Economics and Indirect Rule in Corsica. (May 2021) - Siroky, David S.; Mueller, Sean; Fazi, André; Hechter, Michael
Central governments in multinational states frequently deploy indirect rule to contain peripheral nationalism. Through the exchange of economic resources for political control, local notables are co-opted into cementing loyalty to the central state. Although nationalism often has cultural roots, these can fail to bear fruit because indirect rulers prevent them from developing. When the incentives sustaining support for indirect rulers change, this can open a window of opportunity for nationalism. This article examines how culture, institutions and economics influence center-periphery relations, specifically the demand for autonomy and nationalist parties. Utilizing new, disaggregated data and an original survey from the French island of Corsica, we show that indirect rulers have managed to contain nationalist parties in culturally distinct communes, specifically those that are more dependent on public funds. Only where a thriving private sector offers alternatives to state dependence, lessening the force of indirect rule, is cultural distinctiveness associated with nationalist voting.